2012
DOI: 10.1093/annonc/mdr047
|View full text |Cite
|
Sign up to set email alerts
|

A cytokine and angiogenic factor (CAF) analysis in plasma for selection of sorafenib therapy in patients with metastatic renal cell carcinoma

Abstract: Using CAF profiling, we identified two mRCC patient groups, a candidate plasma signature for predicting PFS benefit, and distinct marker changes occurring with each treatment. This platform may provide valuable insights into renal cell carcinoma biology and the molecular consequences of targeted therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
1
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 35 publications
4
95
1
4
Order By: Relevance
“…3B), consistent with the greater activity of ligand neutralization. Increased circulating VEGF concentrations have been observed with multiple inhibitors of angiogenic signaling pathways (5,16), and were confirmed in this patient cohort (6). Consistent with this, we found decreased tissue pERK at 2 weeks correlated with higher circulating VEGF concentration at both 2 and 6 weeks (r ϭ Ϫ0.60, p ϭ 0.024; r ϭ Ϫ0.63, p ϭ 0.0501, respectively; Table III).…”
Section: Resultssupporting
confidence: 88%
“…3B), consistent with the greater activity of ligand neutralization. Increased circulating VEGF concentrations have been observed with multiple inhibitors of angiogenic signaling pathways (5,16), and were confirmed in this patient cohort (6). Consistent with this, we found decreased tissue pERK at 2 weeks correlated with higher circulating VEGF concentration at both 2 and 6 weeks (r ϭ Ϫ0.60, p ϭ 0.024; r ϭ Ϫ0.63, p ϭ 0.0501, respectively; Table III).…”
Section: Resultssupporting
confidence: 88%
“…Furthermore, it was confirmed that the development of other adverse events like HT (2,18), interstitial pneumonia (19) and a particular range of adverse events (1) was associated with the clinical outcome upon treatment with other molecular-targeted drugs. Although a variety of factors predictive of the clinical outcome upon treatment with sorafenib have been presented (10,11,20,21), all of these studies only focused on the variable of tumor grade. However, the combination of tumor-related factors and host-related factors represented by adverse events can be expected to enable more accurate estimation of the clinical outcome of sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…Specimens were obtained before the initiation of palliative chemotherapy. A total of 52 CAFs present in serum were analyzed with multiplex bead suspension array kits by means of the Bio-Plex 200 system according to the manufacturer's instructions (Bio-Rad Laboratories, Hercules, CA, USA), including human group I and group II cytokine panels as described in previous reports [21,22]. Serum concentrations of soluble carbonic anhydrase IX, soluble vascular endothelial growth factor receptor 2, placental growth factor, and osteopontin were determined by enzyme-linked immunosorbent assay (R&D Systems, Minneapolis, MN, USA).…”
Section: Sample Preparation and Caf Analysismentioning
confidence: 99%